The affinity of mangrove species using Association and Cluster Index in North Coast of Jakarta and Segara Anakan of Cilacap, Indonesia - Endang Hilmi; Lilik Kartika Sari; Tri Nur Cahyo; Muslih MUSLIH; Arif Mahdiana; Sesilia Rani Samudra (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hilmi E, Sari LK, Cahyo TN, Muslih, Mahdiana A, Samudra SR. 2021. The affinity of mangrove species using Association and Cluster Index in North Coast of Jakarta and Segara Anakan of Cilacap, Indonesia. Biodiversitas 22: 2907-2920. The affinity of mangrove species using association and cluster index describe relationship among mangrove species. The species association and clustering explain the degree of utilization of resources and space by mangrove species. The association and cluster also describe specific species adaptation in mangrove ecosystems. This paper was aimed to analyze species affinity using association and clustering index of mangrove species. The association index used Chi-square equation and the clustered index used Euclidian distance analysis. The results showed that (i) mangrove density in Segara Anakan (166-4000 trees ha-1) > North Jakarta (220-1100 trees ha-1). (ii) Nypa fruticans, Avicennia marina, Rhizophora stylosa and Rhizophora apiculata dominated in Segara Anakan of Cilacap, and Rhizophora stylosa and Avicennia marina dominated in North Jakarta (iii) The association index had 12 pairs of negative species association and 17 pairs of positive species association, but most of mangrove vegetations had no association. (iv) mangrove ecosystem in Segara Anakan and North Jakarta had four clusters with Euclidean distance (ED score) 484 to describe cluster between Bruguiera parviflora-Bruguiera sexangula until 76430847 to describe cluster among Bruguiera gymnorrhiza, Bruguiera parviflora, Ceriops decandra, Exoecaria agallocha, Nypa fruticans, Ceriops tagal, Rhizophora stylosa, and Sonneratia caseolaris